2010
DOI: 10.1161/circresaha.110.219493
|View full text |Cite|
|
Sign up to set email alerts
|

The Neuropeptide Catestatin Acts As a Novel Angiogenic Cytokine via a Basic Fibroblast Growth Factor–Dependent Mechanism

Abstract: Rationale:The neuropeptide catestatin is an endogenous nicotinic cholinergic antagonist that acts as a pleiotropic hormone.Objective: Catestatin shares several functions with angiogenic factors. We therefore reasoned that catestatin induces growth of new blood vessels. Methods and Results:Catestatin induced migration, proliferation, and antiapoptosis in endothelial cells and exerted capillary tube formation in vitro in a Matrigel assay, and such effects were mediated via G protein, mitogen-activated protein ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(97 citation statements)
references
References 34 publications
(18 reference statements)
2
93
0
2
Order By: Relevance
“…[ 53 ] In addition, CGA, the protein from which CAT is derived, was shown to be upregulated by hypoxia in neuronal cells after transient hypoxia, [ 54 ] a typical characteristic of angiogenic factors like vascular endothelial growth factor (VEGF). In order to investigate both biocompatibility and the angiogenic potential of the fi lms, HUVECs were seeded on the (PAR/HA) 24 +CAT and compared with control surfaces, tissue culture poly(styrene (TCPS), and (PAR/HA) 24 .…”
Section: Biocompatibility Tests Of Huvec Cells On Par/ha+cat Filmsmentioning
confidence: 99%
“…[ 53 ] In addition, CGA, the protein from which CAT is derived, was shown to be upregulated by hypoxia in neuronal cells after transient hypoxia, [ 54 ] a typical characteristic of angiogenic factors like vascular endothelial growth factor (VEGF). In order to investigate both biocompatibility and the angiogenic potential of the fi lms, HUVECs were seeded on the (PAR/HA) 24 +CAT and compared with control surfaces, tissue culture poly(styrene (TCPS), and (PAR/HA) 24 .…”
Section: Biocompatibility Tests Of Huvec Cells On Par/ha+cat Filmsmentioning
confidence: 99%
“…It functions in many diferent processes within the body including secretion of histamine from mast cells, defense against microbes, vasodilation, and atraction of monocytes. It has also been observed that catestatin acts in a proangiogenic capacity, involved in inducing proliferation and migration of endothelial cells Physiologic and Pathologic Angiogenesis -Signaling Mechanisms and Targeted Therapyas well as formation of capillary tubes [49,50]. This is accomplished through stimulating release of bFGF, which in turn will activate MAPK via binding to FGFR-1 as previously discussed [49,50].…”
Section: Catestatinmentioning
confidence: 86%
“…This is accomplished through stimulating release of bFGF, which in turn will activate MAPK via binding to FGFR-1 as previously discussed [49,50]. It has also been shown that catestatin activates other signal cascades such as PI3K/Akt, serving an anti-apoptotic role to promote cell survival [50].…”
Section: Physiologic and Pathologic Angiogenesis -Signaling Mechanismmentioning
confidence: 93%
See 1 more Smart Citation
“…Moreover a positive effect of CST on monocyte migration in-vitro and the induction of angiogenesis, arteriogenesis and vasculogenesis in the unilateral mouse hind limb ischemia model by a basic fibroblast growth factor (bFGF)-dependent mechanism has been demonstrated (Egger et al, 2008;Theurl et al, 2010). Based on the above-mentioned 70 findings, it is clear that CST exerts a protective and proangiogenetic role via the activation of survival kinases.…”
Section: Introductionmentioning
confidence: 92%